The Effect of the Covid-19 Pandemic on Stock Returns with Moderating Variables of Cash Holding and Earnings Management - Surya Dwi Kurniawan; Eka Bertuah (Politeknik APP Jakarta, 2023)
This study aims to determine the impact of the COVID-19 pandemic in Indonesia on company cash holdings, earnings management practices, and stock returns. To overcome this, a parameter estimation method can be used by adding weight to each parameter, namely the Generalized Least Square (GLS) method. The results showed that the covid-19 pandemic had a significant negative impact on the company's cash holding as a consequence of the company's decreased ability to generate profits. The value of P>|z| shows the number 0.109 which means that the variable has no significant effect. The results of the hypothesis test show that cash holding significant effect on earnings management. At the same time, the company's long-term stock returns are not significantly affected by the COVID-19 pandemic. Earning management practices are also not proven to significantly affect stock returns.